THE IMPLEMENTATION OF SUBSIDIZED FERTILIZER POLICY AT THE DEPARTMENT OF HORTICULTURE AND PLANTATION CROPS IN SINJAI DISTRICT - Linda Irmalasari; Muhammad Luthfi; Baharuddin Baharuddin (Jurnal Administrasi dan Kebijakan Publik, 2024)
The provision of subsidy fertilizers for farmers is intended to increase progress in innovation changes in human resource development in the agricultural sector, subsidies as a supporting factor of optimal implementation of government policies against subsidized fertilizer policies developed by the government based on the needs of the community, especially farmers. In its application, this fertilizer is intended for farmers to increase productivity and improve economic level, also minimizes costs. The purpose of this study is to find out how the implementation of subsidized fertilizer policy in Indonesia. The findings in this study are one of the programs of government policy related to subsidized fertilizers, namely the farmer card program registered in the Group Needs Definitive Plan (RDDK) system. However, according to surveys, there is still a scarcity of subsidized fertilizers so that the price becomes expensive. And many farmers who are not part of the Group Needs Definitive Plan (RDDK) system also need subsidized fertilizers, but the government only provides them to farmers who are members of the RDDK system. In addition, the Indonesian government has implemented various measures to ensure the distribution of subsidized fertilizers to farmers, one of the steps taken is to socialize changes in subsidized fertilizer policies.